Pengaruh Katalis Asam (H2SO4) dan Suhu Reaksi pada Reaksi Esterifikasi Minyak Biji Karet - Mira Primasari, Orchidea Rachmaniah dan M. Rachimoellah, Fitri Yuliani, Mira Primasari, Orchidea (Jurnal Teknik Kimia, 2008)
Biodiesel productions, generally, use transesterification reaction with base as a catalyst. Thus reaction process will be need raw materials oils in high grade quality. Oils with high content of free fatty acids are not suitable for base-catalyzed transesterification reaction. Because of the difficulty of separation process for purify biodiesel or methyl ester from its mixture in the end of the processes. Rubber seed, until now, still underutilized specially in Indonesia which is has an abundant amount of rubber plantation. Rubber seed contain 40-50%-w of oil, which is potentially use as a raw material for biodiesel production. Use an edible oils, unexpensive materials would be minimized the biodiesel production cost in order to produce high quality of biodiesel with competitive market price. Biodiesel production process which is using rubber seed oil high free fatty acid content as a raw material should be decrease the free fatty acids level in to 2%-FFA orless via esterterification methode. Following with transesterification, afterwards. This research desiged to investigate the effects of catalyst amounts (H2SO4) and temperature reaction of esterification methode. Experiment results show that increasing on temperature reaction would be decresed free fatty acids content. 0,5%-w of acid catalyst amount decreased free fatty acids contents rapidly. There are 1,57% and 1,33%-FFA in 120 minute reaction time, 55 oC and 60oC temperature reaction respectively. For others amount of acid catalyst (0,25%, 1%, and 2%-w), thedecresed level of free acid content were work slowly. Respectively, 3,91; 3,16; and 2,62%-FFA for 0,25%, 1%, and 2%-w of acid catalyst amounts. Esterification reaction conditions: 60oC and 0,5%-w of H2SO4 given the higher FAME content. Keywords : biodiesel, acid-catalyzed transesterification, Hevea brasiliensis, rubber seed oil, basecatalyzed transesterification.